Public health in Sudan: priorities, challenges, and pathways to resilience in crisis - Alsoukhni, Majd A.; Aziz, Muna Ibrahim Abdel; Qosa, Haytham; Bani, Ibrahim; Omar, Maye; Elhassan, Muntasir Mohammed Osman; Abbas, Haitham Bashier; Khader, Yousef; Al-Gunaid, Magid; Al Nsour, Mohannad (Frontiers in Public Health, 2025)
In April 2023, the armed conflict erupted in Sudan, exacerbating the ongoing crisis with widespread violence, health system collapse, and outbreaks of vaccine-preventable, vector-borne, and water-borne diseases. Despite these devastating consequences, the international response has been inadequate, requiring urgent advocacy for increased global support. During the EMPHNET 8th Regional Conference (September 15–18, 2024), a 2-hour forum, “Public Health in Sudan: Priorities and Solutions,” brought together a moderator and six distinguished speakers to discuss critical aspects of the health crisis. The forum addressed four key areas: the health and humanitarian needs in Sudan, strategies for building a resilient health system, the role of multisectoral coordination and integrated policies, and the contributions of local and international actors in crisis response and resource mobilization. Key recommendations emphasized strengthening supply chains, decentralizing resources, and fostering multisectoral collaboration to address health determinants and optimize response efforts. Building health system resilience through training, capacity development, and community-based health solutions was identified as critical. The panel also advocated for sustained, conflict-sensitive funding mechanisms and preventive care to improve public health in Sudan. In conclusion, the discussions highlight the importance of integrating health system resilience into recovery plans and fostering strong partnerships to ensure a health system that is adaptable, inclusive, and sustainable. By addressing immediate needs and preparing for future crises, Sudan can build a robust healthcare system capable of withstanding prolonged challenges.